Quantification of Leishmania (Viannia) Kinetoplast DNA in Ulcers of Cutaneous Leishmaniasis Reveals Inter-site and Inter-sampling Variability in Parasite Load. - Milagros Suárez; Braulio M Valencia; Marlene Jara; Milena Alba; Andrea K Boggild; Jean-Claude Dujardin; Alejandro Llanos-Cuentas; Jorge Arevalo; Vanessa Adaui (Public Library of Science (PLoS), 2015)
Cutaneous leishmaniasis (CL) is a skin disease caused by the protozoan parasite Leishmania. Few studies have assessed the influence of the sample collection site within the ulcer and the sampling method on the sensitivity of parasitological and molecular diagnostic techniques for CL. Sensitivity of the technique can be dependent upon the load and distribution of Leishmania amastigotes in the lesion.We applied a quantitative real-time PCR (qPCR) assay for Leishmania (Viannia) minicircle kinetoplast DNA (kDNA) detection and parasite load quantification in biopsy and scraping samples obtained from 3 sites within each ulcer (border, base, and center) as well as in cytology brush specimens taken from the ulcer base and center. A total of 248 lesion samples from 31 patients with laboratory confirmed CL of recent onset (≤3 months) were evaluated. The kDNA-qPCR detected Leishmania DNA in 97.6% (242/248) of the examined samples. Median parasite loads were significantly higher in the ulcer base and center than in the border in biopsies (P<0.0001) and scrapings (P = 0.0002). There was no significant difference in parasite load between the ulcer base and center (P = 0.80, 0.43, and 0.07 for biopsy, scraping, and cytology brush specimens, respectively). The parasite load varied significantly by sampling method: in the ulcer base and center, the descending order for the parasite load levels in samples was: cytology brushes, scrapings, and biopsies (P<0.0001); in the ulcer border, scrapings had higher parasite load than biopsies (P<0.0001). There was no difference in parasite load according to L. braziliensis and L. peruviana infections (P = 0.4).Our results suggest an uneven distribution of Leishmania amastigotes in acute CL ulcers, with higher parasite loads in the ulcer base and center, which has implications for bedside collection of diagnostic specimens. The use of scrapings and cytology brushes is recommended instead of the more invasive biopsy.